Patterns of Change in 18th-century English. A sociolinguistic approach - Minna Palander-Collin (Advances in Historical Sociolinguistics, 2018)
Eighteenth-century English is often associated with normative grammar. But to what extent did prescriptivism impact ongoing processes of linguistic change? The authors of this volume examine a variety of linguistic changes in a corpus of personal correspondence, including the auxiliary do, verbal -sand the progressive aspect, and they conclude that direct normative influence on them must have been minimal. The studies are contextualized by discussions of the normative tradition and the correspondence corpus, and of eighteenth-century English society and culture. Basing their work on a variationist sociolinguistic approach, the authors introduce the models and methods they have used to trace the progress of linguistic changes in the "long" eighteenth century, 1680-1800. Aggregate findings are balanced by analysing individuals and their varying participation in these processes. The final chapter places these results in a wider context and considers them in relation to past sociolinguistic work. One of the major findings of the studies is that in most cases the overall pace of change was slow. Factors retarding change include speaker evaluation and repurposing outgoing features, in particular, for certain styles and registers.